Transitional Justice in Eastern Europe and the former Soviet Union: Reckoning with the communist past - Stan, Lavinia (Routledge, 2010)
During the last two decades, the countries of Eastern Europe and the former Soviet Union have attempted to address the numerous human rights abuses that characterized the decades of communist rule. This book examines the main processes of transitional justice that permitted societies in those countries to come to terms with their recent past. It explores lustration, the banning of communist officials and secret political police officers and informers from post-communist politic, ordinary citizens’ access to the remaining archives compiled on them by the communist secret police, as well as trials and court proceedings launched against former communist officials and secret agents for their human rights trespasses. Individual chapters explore the progress of transitional justice in Germany, the Czech Republic, Slovakia, Poland, Hungary, Romania, Bulgaria, Albania, Slovenia and the successor states of the former Soviet Union. The chapters explain why different countries have employed different models to come to terms with their communist past; assess each country’s relative successes and failures; and probe the efficacy of country-specific legislation to attain the transitional justice goals for which it was developed. The book draws together the country cases into a comprehensive comparative analysis of the determinants of post-communist transitional justice, that will be relevant not only to scholars of post-communist transition, but also to anyone interested in transitional justice in other contexts.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Sorry States: Apologies in International Politics - Lind, Jennifer (Cornell University Press, 2010)
Governments increasingly offer or demand apologies for past human rights abuses, and it is widely believed that such expressions of contrition are necessary to promote reconciliation between former adversaries. The post-World War II experiences of Japan and Germany suggest that international apologies have powerful healing effects when they are offered, and poisonous effects when withheld. West Germany made extensive efforts to atone for wartime crimes-formal apologies, monuments to victims of the Nazis, and candid history textbooks; Bonn successfully reconciled with its wartime enemies. By contrast, Tokyo has made few and unsatisfying apologies and approves school textbooks that whitewash wartime atrocities. Japanese leaders worship at the Yasukuni Shrine, which honors war criminals among Japan's war dead. Relations between Japan and its neighbors remain tense.Examining the cases of South Korean relations with Japan and of French relations with Germany, Jennifer Lind demonstrates that denials of past atrocities fuel distrust and inhibit international reconciliation. In Sorry States, she argues that a country's acknowledgment of past misdeeds is essential for promoting trust and reconciliation after war. However, Lind challenges the conventional wisdom by showing that many countries have been able to reconcile without much in the way of apologies or reparations. Contrition can be highly controversial and is likely to cause a domestic backlash that alarms?rather than assuages?outside observers. Apologies and other such polarizing gestures are thus unlikely to soothe relations after conflict, Lind finds, and remembrance that is less accusatory-conducted bilaterally or in multilateral settings-holds the most promise for international reconciliation.
Keywords: References - Boel et al. (2021); Archives and Human Rights

The Gacaca Courts, Post-Genocide Justice and Reconciliation in Rwanda: Justice without Lawyers - Clark, Phil (Cambridge University Press, 2010)
This is a timely empirical study and review of the Gacaca Courts which were established in 2001 in Rwanda as an attempt to prosecute suspects involved in the 1994 genocide. Based on the author's original field work which began in 2003 in Rwanda and which has been updated to the end of 2009, it includes responses from within the Rwandan population. Dr. Clark argues that, despite widespread international scepticism, the Gacaca process has achieved remarkable results in terms of justice and reconciliation, although this has often come at a price, especially the re-traumatisation of many Rwandans who have participated firsthand in hearings. This book will appeal to a wide global readership crossing human rights, transitional justice and African studies for its combination of original empirical data with a socio-legal analysis.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Unspeakable Truths: Transitional Justice and the Challenge of Truth Commissions - Hayner, Priscilla B. (Routledge, 2010)
In a sweeping review of forty truth commissions, Priscilla Hayner delivers a definitive exploration of the global experience in official truth-seeking after widespread atrocities. When Unspeakable Truths was first published in 2001, it quickly became a classic, helping to define the field of truth commissions and the broader arena of transitional justice. This second edition is fully updated and expanded, covering twenty new commissions formed in the last ten years, analyzing new trends, and offering detailed charts that assess the impact of truth commissions and provide comparative information not previously available.Placing the increasing number of truth commissions within the broader expansion in transitional justice, Unspeakable Truths surveys key developments and new thinking in reparations, international justice, healing from trauma, and other areas. The book challenges many widely-held assumptions, based on hundreds of interviews and a sweeping review of the literature. This book will help to define how these issues are addressed in the future.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Austerlitz - Sebald, W.G. (Penguin, 2010)
Keywords: References - Boel et al. (2021); Archives and Human Rights

The Emergence of Memory: Conversations with W. G. Sebald - Sebald, W. G. (Seven Stories Press, 2010)
When German author W. G. Sebald died in a car accident at the age of fifty-seven, the literary world mourned the loss of a writer whose oeuvre it was just beginning to appreciate. Through published interviews with and essays on Sebald, award-winning translator and author Lynne Sharon Schwartz offers a profound portrait of the writer, who has been praised posthumously for his unflinching explorations of historical cruelty, memory, and dislocation. With contributions from poet, essayist, and translator Charles Simic, New Republic editor Ruth Franklin, Bookworm radio host Michael Silverblatt, and more, The Emergence of Memory offers Sebald’s own voice in interviews between 1997 up to a month before his death in 2001. Also included are cogent accounts of almost all of Sebald’s books, thematically linked to events in the contributors’ own lives.Contributors include Carole Angier, Joseph Cuomo, Ruth Franklin, Michael Hofmann, Arthur Lubow, Tim Parks, Michael Silverblatt, Charles Simic, and Eleanor Wachtel.
Keywords: References - Boel et al. (2021); Archives and Human Rights